Game-based element within rehabilitation program: Case study at community-based centers (PDKs in Putrajaya, Malaysia) - Latif R.A.; Mahidin E.M.M.; Ismail R. (IOS Press, 2023)
Occupational therapy; Disability; Game-Based; Intervention programs; Music therapy; Rehabilitation programs; Patient treatment